Amyloid-related protein changes associated with dementia differ according to severity of hypoglycemia. Issue 1 (30th April 2021) - Moin, Abu Saleh Md; Kahal, Hassan; Al-Qaissi, Ahmed; Kumar, Nitya; Sathyapalan, Thozhukat; Atkin, Stephen L; Butler, Alexandra E
Abstract : Introduction: Hypoglycemia in type 2 diabetes (T2D) may increase risk for Alzheimer's disease (AD), but no data on changes in AD-related proteins with differing degrees of hypoglycemia exist. We hypothesized that milder prolonged hypoglycemia would cause greater AD-related protein changes versus severe transient hypoglycemia. Research design and methods: Two prospective case-control induced hypoglycemia studies were compared: study 1, hypoglycemic clamp to 2.8 mmol/L (50 mg/dL) for 1 hour in 17 subjects (T2D (n=10), controls (n=7)); study 2, hypoglycemic clamp to 2.0 mmol/L (36 mg/dL) undertaken transiently and reversed in 46 subjects (T2D (n=23), controls (n=23)). Blood sampling at baseline, hypoglycemia and 24-hour post-hypoglycemia, with proteomic analysis of amyloid-related proteins performed. Results: In control subjects, the percentage change from baseline to hypoglycemia differed between study 1 and study 2 for 5 of 11 proteins in the AD-related panel: serum amyloid A1 (SAA1) (p=0.009), pappalysin (PAPPA) (p=0.002), apolipoprotein E2 (p=0.02), apolipoprotein E3 (p=0.03) and apolipoprotein E4 (p=0.02). In controls, the percentage change from baseline to 24 hours differed between studies for two proteins: SAA1 (p=0.003) and PAPPA (p=0.004); however, after Bonferroni correction only SAA1 and PAPPA remain significant. In T2D, there were no differential protein changes between the studies. Conclusions: The differential changes in AD-related proteins were seen only in control subjects in response to iatrogenic induction of hypoglycemic insults of differing length and severity and may reflect a protective response that was absent in subjects with T2D. Milder prolonged hypoglycemia caused greater AD-related protein changes than severe acute hypoglycemia in control subjects. Trial registration numbers: NCT02205996, NCT03102801 .